Between fit and flexibility? The benefits of high‐performance work practices and leadership capability for innovation outcomes. (7th August 2020) - Gahan, Peter; Theilacker, Max; Adamovic, Mladen; Choi, Daejeong; Harley, Bill; Healy, Joshua; Olsen, Jesse E.
Abstract: The idea that human resource management (HRM) plays a strategic role in generating sustainable competitive advantage for organisations or intermediate outcomes such as innovation is a central tenet in HRM theory and research. Yet, the explanation for this relationship remains unclear. We contribute to understanding how HRM plays a role by integrating insights drawn from HRM and strategic management. We explore how configurations of high‐performance work systems (HPWS) and leadership competence (LC) provide micro‐foundations for organisational capabilities associated with innovation. We also examine the moderating role of external environmental conditions. We find support for the proposition that HPWS and LC contribute to capabilities associated with innovation. Importantly, in stable environments, the formation of the capabilities required for innovation is more strongly associated with HPWS, whereas in more dynamic environments, LC plays a more pronounced role. These findings have implications for understanding the strategic role HRM plays and for management practice.